2015
DOI: 10.1016/j.jacc.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Frailty and Risk of Cardiovascular Disease in Elderly Men and Women

Abstract: Our findings suggest that pre-frailty, which is potentially reversible, is independently associated with a higher risk of older adults developing CVD. Among the physical domains of pre-frailty, low gait speed seems to be the best predictor of future CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
159
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 42 publications
8
159
1
3
Order By: Relevance
“…In a cohort of older British men, Fried's criterion of pre-frailty and frailty was significantly associated with hypertension in a cross-sectional analyses, although the relationship was not significant in subjects without established cardiovascular disease [21]. In Sergi's cross-sectional analyses, pre-frailty was significantly associated with high SBP, and marginally associated with hypertension [22]. However, using the same definition, frailty and pre-frailty were negatively associated with BP in the Brazilian population [23].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a cohort of older British men, Fried's criterion of pre-frailty and frailty was significantly associated with hypertension in a cross-sectional analyses, although the relationship was not significant in subjects without established cardiovascular disease [21]. In Sergi's cross-sectional analyses, pre-frailty was significantly associated with high SBP, and marginally associated with hypertension [22]. However, using the same definition, frailty and pre-frailty were negatively associated with BP in the Brazilian population [23].…”
Section: Discussionmentioning
confidence: 91%
“…A longitudinal study recently reported that pre-frailty diagnosed based on Fried's biological syndrome model criterion was also significantly associated with cardiovascular events [22]. Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of pre-frailty as a unique phenotype has gained increasing recognition, and ours is the first study to define the prevalence of pre-frailty in patients treated with TAVI. 1,13 Previous reports have identified frailty in 15% to 49% of patients treated with TAVI, but those reports did not assess for pre-frailty as a unique classification. 5,7 We found that the largest proportion of patients treated with TAVI were classified as pre-frail (37%), which has important implications for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate that early detection of a pre-frail state may offer a therapeutic window to reduce frailty-associated morbidity and mortality. 13,18 Fried et al 1 showed that, after adjusting for confounders, patients with pre-frailty have double the risk of developing incident frailty compared with patients without frailty over 3 years. Among patients with pre-frailty, TAVI may offer an opportunity to reverse the development of frailty and improve important geriatric end-points, such as independence and functional capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation